Methodological Aspect of Women Empowerment and Socio-economic Development - Chompa, Mousumi Yasmin (Patan Prospective Journal, 2022)
The purpose of this paper is to analyzemethodological aspect of women empowerment and socio economic development. Methodology is a methods of a research or a framework for a researchalso the philosophical discussion of related structural assumptionswhich is based on views and beliefs. Women empowerment is the strategies of women to increase their control of resources and generate decision making capacity. Socio-economic development is the processes of social and economic development that is measured with GDP, life expectancy, literacy and levels of employment indicators. The finding shows that quantitative and qualitative approach are considered as the most significant research methods in methodology. Quantitative research is the main methodology of natural sciencesresearch which is used for numerical measurements. Qualitative research is assigned of social sciences research and concerned with the human behavior and experience, itis focused more at an in-depth understanding of the meaning of the studied phenomena and offered less prominence to numerical measurements.